ANALISIS SWOT SEBAGAI DASAR DALAM MENENTUKAN STRATEGI PEMASARAN PADA PERUSAHAAN PT.HARMONY TOBA JAYA MEDAN - Siregar, Ninny (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
PT.  Harmony  Toba  Jaya  is  one  of  the  paint  distributor  with  Sikkens  trademark. Companies  choose  direct  communication  with  consumers  workshops  in  their  marketing communications strategy. This is done because of the increasing number of new paint products on the market so we need a strategy that is relevant to the condition that there is a bottom -up with a marketing strategy where marketers sell products directly to end users or workshop. Based on the above conditions need to be processing data analysis using SWOT analysis (Strength,  Weakness, Opportunity and Threat) from Sikkens paint products through questionnaires given to consumers. Based on the results of the questionnaire processing, can be calculated the value of the X axis and Y axis to determine the position of the company. The value of  the X-  and Y-axis respectively is -0.141 and  -0.100 so that the value of the intersection of the axes X and Y are XY (-0.141;  -0.100). From these  results,  the  company  is  located  in  Quadrant  IV  (negative,  negative).  It  is  necessary  to  get attention  because  in  addition  to  the  weakness  of  the  company  there  are  also  threats  from competitors  that  are  very  dangerous.  Therefore,  recommendations  given  strategy  is  Strategy Defense,  meaning  that  the  internal  conditions  of  the  organization  that  are  in  selection  dilemma. Therefore, organizations are advised to use a survival strategy, the performance of internal control so as not to fall. This strategy is maintained while trying to fix ourselves.Keywords: Marketing Strategy, SWOT Analysis, Company Position